Life Expectancy and its Determinants in the Czech Republic - Vojtech Korbelius; Michal Paulus; Tomas Troch (Charles University in Prague, Institute of Economic Studies (IES), 2016)
We model the life expectancy function for the Czech Republic using three types of explanatory variables: socio-economic, healthcare and environmental pollution factors. The paper presents the first life expectancy model of the Czech Republic and contributes to the existing literature also by the analysis of district level data and inclusion of environmental pollution variables. We found two qualitatively different life expectancy functions where one is applicable for men at the age of 45 and 65 and women at the age of 45 and the other is suitable for women at the age of 65. Key findings can be summarized as follows: only one healthcare factor was significant in all models simultaneously and environmental pollution factors were revealed as significant and should be included in other models of life expectancy function.
Keywords: 330; Sterblichkeit; Gesundheitswesen; Umweltbelastung; Schätzung; Tschechien